Akuisisi Ruang Perkotaan Sebagai Tempat Bermain Anak: Studi Kasus Pandeyan, Yogyakarta - Siti Nurjannah; Arnis Rochma Harani; Bangun I.R. Harsritanto Harsritanto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: Urban spaces are often used by children as places to play, even if they are not specifically designed for this activity. This research explores how children acquire urban spaces and utilize urban elements as part of their play, with a focus on traditional games in Indonesia. Using a qualitative approach through direct observation in Pandeyan, Yogyakarta, this study found that children show great creativity in appropriating the surrounding environment, such as roads, sidewalks, fences, and open spaces, as play areas. The results show that various city elements have affordances that enable children's exploration and social interaction, but also present challenges related to safety and accessibility. Therefore, designing a more inclusive and child-friendly city needs to consider the balance between structured and spontaneous play spaces. With this understanding, it can serve as a reference to create an environment that is more supportive of children's development, both in terms of physical, social and cognitive aspects. Keyword: urban space, children's play, space acquisition, affordance